Vinhos novos em odres velhos: a influência cristã nas discussões sobre o direito à proteção das religiões indígenas na assembleia nacional constituinte (1987-1988) - Morais, Vitória Larissa Dantas de (Universidade Federal Rural do Semi-Árido, 2020)
Relations between natives and the christian church exist since the period of colonial Brazil and remain active until nowadays. According to the indexes publicized by IBGE about a research carried out between 1991 and 2010, brazilian indigenous people still have high percentages of converts to the christian faith and a low number of adherents to traditional religions. Although the Federal Constitution of 1988 gave a grater cultural protection to indigenous people, it is possible to observe that the legal system does not have norms that could control the entry of religous organizations in indigenous lands, as there is, for example, for the entry of researchers. Due to the perceived blank and aware that the current Federal Constitution is the basis of the entire legal system, an analysis of the events of the National Constituent Assembly (1987/1988) was made to answer the following question: was the right of religion freedom guaranteed to indigenous people in this democratic event? To solve that problem, this research was developed on three fronts: an apresentation of the context that proceded the Constituient Assebly, an analysis of the participation of christian representatives in discussions about indigenous theme, especially the ones involving religion, and the perspectives observed by constituents about the relationship between christianity and natives. Finally, understand how was the indigenous participation in the National Constituent Assembly. The research was predominantly documental and bibliographic, based on Quentin Skinner’s conception of historical contextualism, and Pietro Costa’s considerations about theory and historiography. Lastly, it was possible to conclude the absence of the right of indigenous religious freedom during the Nacional Constituent Assembly due to the under representations of their leaders, as well as the prioritizations, by brazilian State, of the participarions of christian representatives
Keywords: Assembleia nacional constituinte; Liberdade religiosa; Indígena; Nativos; National constituent assembly; Religious freedom; Indígenous; Natives; CIENCIAS SOCIAIS APLICADAS::DIREITO